Parathyroid Hormone Levels Predict Long-Term Outcome After Operative Management of Parathyroid Cancer - Machens, Andreas; Lorenz, Kerstin; Dralle, Henning (Hormone and Metabolic Research, 2017)
The role of parathyroid hormone (PTH) serum levels for prediction of outcome is ill defined for parathyroid cancer, which is a very rare disease. This investigation of 17 consecutive patients with parathyroid cancer, (re-)operated on at a tertiary referral center between 1994 and July 2016, with a mean follow-up of 179.6 months (15 years) aimed to clarify the suitability of PTH serum levels for prediction of clinical outcome after comprehensive operative management of parathyroid cancer. Cancer-specific mortality occurred significantly more often with the performance of sternotomy before or at first operation at this institution (80 vs. 0%; p=0.002); mean PTH serum levels before first operation (1 105 vs. 357 pg/ml; p=0.008; r=0.77) and at most recent follow-up (3 167 vs. 101 pg/ml; p=0.019; r=0.60); and normalization of PTH serum levels at most recent follow-up (0 vs. 64%; p=0.034). For cancer-specific survival, receiver-operating characteristics analysis identified as optimum cut-off point an initial PTH serum level of 700 pg/ml. For local recurrence, no significant associations were found. Kaplan-Meier analysis confirmed that the patients with initial PTH serum levels >700 pg/ml (plog-rank=0.011) and sternotomy (plog-rank<0.001), but not node or lung metastases, had worse cancer-specific survival. Parathyroid cancer is much more an endocrine disease with oncological features than an oncological disease with endocrine features. Operative intervention(s) should be comprehensive and directed at clearing all metabolically active parathyroid tumor deposits early. If surgical cure cannot be reached, it is pivotal to achieve metabolic control, obviating the need for, or facilitating, medical therapy of hypercalcemia, and preserve renal function.
Keywords: parathyroid cancer; intact parathyroid hormone; lymph node metastasis; distant metastasis; locoregional recurrence; long-term survival